2020
DOI: 10.1177/0253717620932243
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Factor Analysis of Young’s Internet Addiction Test Among Professionals from India: An Online Survey

Abstract: Background: Internet use has spread across the world due to easy accessibility and affordability. However, it has been creating many problems at several levels. So, there is a need to identify the suitability of psychometric properties and the factor structure of the widely used Internet Addiction Test (IAT) in the Indian settings. Our objective was to perform an exploratory factor analysis on the IAT and to test the reliability of the scale. Methods: It was a cross-sectional study that included various profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Also, avoid moving from one topic to another throughout the chat, since this may cause them to become confused. The emergency department would also increase the care take of older people by implementation of these ideas and would all together be able to provide a better healthcare facility for older people as a whole federation [8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Also, avoid moving from one topic to another throughout the chat, since this may cause them to become confused. The emergency department would also increase the care take of older people by implementation of these ideas and would all together be able to provide a better healthcare facility for older people as a whole federation [8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on young students in an Indian metro, Kumar and Mondal (2018) found that those with high incidences of internet use demonstrated psychopathological symptoms and a lowered sense of well-being. Further, studies reported that as the individual gets more and more entangled in their uncontrollable desire to engage with the internet, there develops an element of social loneliness (Suresh and Biswas,2019), the aftermath of which is lowered productivity and interpersonal dysfunction (Spoorthy et al , 2020). Demetrovics et al (2008) identified three problem areas associated with internet addiction, namely, a standard definition of the construct and its subsequent measurement, and most importantly, based on these, the identification of diagnostic symptoms that could help identify the level or the extent of the problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Longstreet et al (2019) also asserted that those who lacked emotional stability and a defence mechanism to cope with challenges were more prone to higher levels of addiction. Several researchers studied the roles played by personality and emotions in internet addiction (Spoorthy et al , 2020); however, they obtained mixed results. Alt and Boniel-Nissim (2018) identified that those who were more gregarious and extroverted were more inclined to problematic internet use.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations